2007
DOI: 10.1080/09595230601052777
|View full text |Cite
|
Sign up to set email alerts
|

Zopiclone misuse: an update from Dublin

Abstract: The prevalence of zopiclone misuse in clients attending a methadone maintenance programme in Dublin through detection of its degradation product, 2-amino-5-chloropyridine (ACP) on urinalysis is outlined. Urine samples from all 158 clients were tested for the presence of ACP, opiates, benzodiazepines, cocaine, alcohol and cannabis. Of the 37 (23%) clients who tested positive for ACP, 23 (62%) were interviewed. A profile of zopiclone misusers is outlined, including details of demographics, drug history, viral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…This study strongly supported the misuse potential of z-drugs among people with opioid dependence [16, 17] with almost three-quarters of people who reported z-drug lifetime use also reporting nonmedical use. It is also notable that a quarter of those who reported lifetime pregabalin use used it for recreational purposes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study strongly supported the misuse potential of z-drugs among people with opioid dependence [16, 17] with almost three-quarters of people who reported z-drug lifetime use also reporting nonmedical use. It is also notable that a quarter of those who reported lifetime pregabalin use used it for recreational purposes.…”
Section: Discussionsupporting
confidence: 75%
“…This is the case for the so-called z-drugs, benzodiazepine-like hypnotics including zolpidem, zaleplon, and zopiclone [16, 17], as well as the anxiolytic drug pregabalin [18]. In a study in Ireland, 23% of patients in methadone maintenance treatment (MMT) were using z-drugs nonmedically [16]. The percentage of nonmedical pregabalin use among patients in OMT has been estimated at 3–12% in previous studies [1822].…”
Section: Introductionmentioning
confidence: 99%
“…Zopiclone, a short acting hypnotic drug used for treatment of insomnia, is a common finding in forensic cases [1][2][3][4][5][6][7] and it is frequently analyzed in biological materials using different analytical methods. Analysis of zopiclone in biological specimens is complicated by its instability in certain solvents e.g.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years there have been an increasing number of reports about the abuse and misuse of ZOP [90]. One study showed a prevalent misuse of ZOP when its degradation product 2-amino-5-chloropyridine (ACP) was detected in urine [69]. In Sweden, the first petty drug offences involving ZOP appeared 1994.…”
Section: Occurrence Of Zopiclone In Forensic Casesmentioning
confidence: 99%
“…The drug was introduced for treatment of insomnia in the 1980s and was registered in Sweden in 1991. ZOP is increasingly being encountered in forensic cases and is a common finding in samples from drug-impaired drivers, users of illicit recreational drugs, victims of drug facilitated sexual assaults and forensic autopsy cases [25,[69][70][71][72][73][74][75][76]. ZOP is considered a non-benzodiazepine from the cyclopyrrolone class.…”
Section: Zopiclonementioning
confidence: 99%